The Role of Self-Esteem in Individuals Experiencing Toxic Relationships - Alfaiyini Hidayati Abdullah; Djudiyah; Siti Suminarti Fasikhah (Kirana Publisher (KNPub), 2026)
A toxic relationship is an interpersonal relationship characterized by unhealthy interaction patterns and the potential for negative psychological impacts on individuals such us low self-esteem. This study aims to systematically examine the role of self-esteem in individuals experiencing toxic relationships through a systematic literature review (SLR). The review process followed the PRISMA guidelines, with planning, implementation, and reporting stages. A literature search strategy was conducted in several scientific databases, namely Ebsco, ERIC, SagePub, ResearchGate, Taylor & Francis Online, and Wiley Online Library using the keywords self-esteem, self-worth, and toxic relationships. Of the 286 articles identified, 10 met the inclusion criteria for further analysis. The synthesis results show that self-esteem has three main roles: as a factor in an individual's vulnerability to involvement in toxic relationships, as a psychological consequence of unhealthy relationship experiences, and as a protective factor that increases an individual's resilience and psychological well-being. Individuals with low self-esteem are more vulnerable to maintaining detrimental relationships, while high self-esteem contributes to adaptive coping skills, psychological recovery, and the formation of healthier relationships. These findings emphasize the importance of psychological interventions based on strengthening self-esteem as a preventive and curative strategy for victims of toxic relationships.